What a dog transmissible tumor can teach us about cancer regression. (4th July 2018) - Fassati, Ariberto
ABSTRACT: The canine transmissible venereal tumor (CTVT) is one of the few clonally transmissible cancers in nature and the only one that fully regresses following treatment with vincristine. The molecular signature of CTVT regression has been described in a recent paper published in Cancer Cell, revealing some fundamental insights into cancer regression.